Adsorption Study of Cobalt on Treated Granular Activated Carbon - Y. V. Hete; S. B. Gholase; R. U. Khope (E-Journal of Chemistry)
This study is carried out for the removal of cobalt from aqueous solution using granular activated carbon in combination with p-nitro benzoic acid at temperature 25±1 °C. The adsorption isotherm of cobalt on granular activated carbon has been determined and the data fitted reasonably well to the Langmuir and Freundlich isotherm for activated carbon.